The “misery of prison” and the “prison of misery” in contemporary Brazil - Santos, Paulo Roberto Felix (Argumentum, 2020)
The current scenario, marked by the capitalist crisis, the rise of neoliberalism and the deepening of social inequalities, demonstrates the hypertrophy of the penal state and the increase in the Brazilian prison population. Based on critical Marxist criminology and the analysis of data on the prison system in the country, we seek to question how this space has been configured, and the profile of its inmates. In addition to the precarious conditions of the prisons and the permanent violation of rights, there is a criminalization of misery, in view of the profile of the inmates, as well as the selective-racial character, with a majority of young blacks and blacks, reaffirming the structural racism to which this population is subjected. Thus, alternatives are required in addition to prisons, and the construction of other forms of social organization, which do not reproduce the inequalities that prison intends to control. Keywords: Capitalism. Penal State. Prison System. Racism. Brazil.